Effects of diluents, dilution ratios and cryoprotectants for the cryopreservation of Thai Sharpunti (Barbodes gonionotus) spermatozoa - Uddowla, MH; Salma, U; Rahman, MM; Hossain, MS; Mollah, MFA (International Journal of Natural Sciences, 2011)
Attempts were made to develop a protocol for the long term cryogenic freezing of Thai sharpunti (Barbodes goininotus) spermatozoa to maintain the gene pool as well as biodiversity. For these purpose, experiments were carried out with three specific objectives i.e., to find out the suitable diluents, dilution ratios (milt: cryodiluents) and suitable cryoprotectants. Effects of as many as 12 diluents and the three cryoprotectants were tested initially for the post thawed spermatozoa motility. Among the 12 diluents which gave more than 50%> motility in equilibrated periods (10-15 mins. of mixing with cryodiluents) were subsequently used for cryopreservation. Urea-egg-yolk as diluents was the most effective among the 12 diluents followed by egg-yolk citrate and Korokura solution. Urea-egg-yolk showed 52.91% spermatozoa motility on its 1st day and 46.87% on 30th day whereas egg-yolk citrate solution showed 46.25% and 38.53% motility on 1st and 30th day respectively. Four dilution ratios 1:3, 1:4, 1:5 and 1:6 were used out of which 1:5 seemed to be most suitable on both of Urea-egg-yolk and egg-yolk citrate. To select the best fraction (%) of cryoprotectants to the diluents trials were given with DMSO, glycerol, ethanol at 10% and a combination of 5% DMSO and 5% glycerol. Ten percent DMSO and combination of 5% DMSO + 5% glycerol was proven best. Proper application of this technology in field could be effective tools for protecting the endangered species in Bangladesh. Key words: Milt; diluents; Spermatozoa; Cryoprotectants; cryopreservation DOI: http://dx.doi.org/10.3329/ijns.v1i2.8820 International Journal of Natural Sciences (2011), 1(2):44-51